Chromatic behavior of acrylic and bisacrylic resins used for provisional restorations - Juan José Christiani; Ricardo Hugo Altamirano; María Teresa Rocha (Editorial Ciencias Médicas, 2021)
Introduction: Provisional prosthesis are restorations used in fixed prostheses for a while, until the definitive prosthesis is cemented. One of the problems posed by this type of restoration is the change in color, which affects esthetics and therefore creates a feeling of displeasure in patients. Objective: Evaluate, in the case of provisional restorations with and without final surface polish, the color stability of two resins when soaked in coffee. Methods: An in vitro experimental study was conducted in the Prosthesis Laboratory at the Dental School of the National University of the Northeast in Corrientes, Argentina, in the year 2019. A comparison was made of an acrylic resin (Duralay®) versus a bisacrylic resin (ProtempIV 3M®) for provisional restorations. Forty resin disks were made from metal molds 2 mm thick and 25 mm in diameter. Twenty disks were used for each type of resin, of which 10 were polished and 10 were not. The samples were stored in distilled water in a stove at 37ºC for 24 h to hydrate them. Color measurements were then taken. Next, each group was soaked in coffee and kept in the stove at 37ºC for another 24 h. A second color measurement was then taken. A Konica Minolta® colorimeter was used to determine total color difference ΔE. Statistical analysis was based on one-way ANOVA and Tukey's test was used to identify the difference between the groups. Results: In the polished acrylic resin group a difference was found of ΔE = 0.82 ± SD = 0.22, whereas in the non-polish group the difference was ΔE = 3.86 ± SD = 0.30. In the polished bisacrylic resin group the difference was ΔE = 4.84 ± SD = 0.25, whereas in the non-polish group the difference was ΔE = 5.85 ± SD = 0.29. Conclusions: Significant differences were found in the color stability of both resins. The bisacrylic resin was the least stable, regardless of polish.